Monkeypox - new epidemiological threat? Review of the current literature - Jarosz, Dominika; Grudzińska, Aleksandra; Dudzińska, Paulina; Milanowska, Małgorzata; Tsitko, Hanna (Journal of Education, Health and Sport, 2023)
The mokeypox is zoonotic disease caused by an orthopoxvirus, which was first isolated and identified in 1959 among captive monkeys transported to Copenhagen, Denmark from Africa for research purposes. Monkeypox in humans was initially diagnosed in 1970 in the Democratic Republic of the Congo and then it has spread to other regions of Africa. The monkeypox cases in Africa were neglected by the scientific community for past decades till 2022, when thousands of cases were reported from nonendemic countries around Europe and in the western hemisphere. Therefore monkeypox has recently been labelled as a public health emergency of international concern by the WHO. Monkeypox virus is believed to have several modes of transmission, all of which are associated with direct or indirect contact with infected animals or infected humans. The diagnosis of monkeypox infection is based on the history, clinical symptoms and laboratory tests such as PCR.The illness begins with nonspecific symptoms such as fever, lethargy, lymphadenopathy, myalgias and then it occures the rash first on the face and then across the body which lasts for 2–4 weeks. Most cases of monkeypox are mild and self-limited disease, which require only supportive treatments. However in very severe cases antiviral medications such as tecovirimat may be administered. Smallpox vaccination has been estimated to provide 85% cross-protection against monkeypox infection. The main problem is there is a huge population born only after the discontinuation of the smallpox vaccination campaign with lack of cross-protective immunity. The question is - the monkeypox is only old neglected foe or a new epidemiological threat?